It Cuts Both Ways: An Annelid Model System for the Study of Regeneration in the Laboratory and in the Classroom - Martinez Acosta, Veronica G.; Arellano-Carbajal, Fausto; Gillen, Kathy; Tweeten, Kay A.; Zattara, Eduardo E. (Frontiers in Cell and Developmental Biology, 2021)
The mechanisms supporting regeneration and successful recovery of function have fascinated scientists and the general public for quite some time, with the earliest description of regeneration occurring in the 8th century BC through the Greek mythological story of Prometheus. While most animals demonstrate the capacity for wound-healing, the ability to initiate a developmental process that leads to a partial or complete replacement of a lost structure varies widely among animal taxa. Variation also occurs within single species based on the nature and location of the wound and the developmental stage or age of the individual. Comparative studies of cellular and molecular changes that occur both during, and following, wound healing may point to conserved genomic pathways among animals of different regenerative capacity. Such insights could revolutionize studies within the field of regenerative medicine. In this review, we focus on several closely related species of Lumbriculus (Clitellata: Lumbriculidae), as we present a case for revisiting the use of an annelid model system for the study of regeneration. We hope that this review will provide a primer to Lumbriculus biology not only for regeneration researchers but also for STEM teachers and their students.